Endoscopic ultrasound-guided hepaticogastrostomy using a 6-F cystotome and 12-cm covered metal stent - Mandai, Koichiro; Uno, Koji; Okada, Yusuke; Suzuki, Azumi; Yasuda, Kenjiro (Endoscopy International Open, 2016)
Background and study aims: An iincreasing number of reports describe endoscopic ultrasound-guided hepaticogastrostomy for malignant biliary obstruction in patients with endoscopic retrograde cholangiopancreatography failure. However, this procedure has not yet been standardized; as a result, the rate of adverse events, including bile leakage and stent migration, is relatively high. Here, we report our experience with four cases of endoscopic ultrasound-guided hepaticogastrostomy performed according to our institutional procedure.